SOSIALISASI PEMANFAATAN LIMBAH PLASTIK MENJADI PAVING BLOCK DI DESA MEDALKRISNA - Apandi, Syahrul; Arrahim, Arrahim; Ramadhan, Fakhran (An-Nizam, 2024)
The social activities that took place in MedalKrisna village aimed to foster resilient and responsible personalities in the community as well as increase the sense of empathy and concern for the community. The goal of this activity is to help the community find solutions to various existing problems, including eliminating plastic waste. Based on the results of surveys, interviews and observations conducted in MedalKrisna village, community awareness regarding waste management is still very low, especially in Hamlet 1 due to the large number of residents and the large amount of plastic waste that has accumulated. This can have a negative impact on the community. Atmosphere. Health & Beauty. Disrupt the maintenance of environmental functions, both in residential areas and in rice fields and rivers. To reduce the amount of plastic waste that is disposed of carelessly, efforts are made to utilise plastic waste for paving. The method used in managing plastic waste is by providing training and discussion as well as providing support to the community in the plastic waste management process. The results of the implementation of the real work lecture (KKN) are that participants can have knowledge and skills in handling plastic waste, especially paving blocks, the making of paving from plastic waste supports government programmes in reducing waste, especially plastic waste, andthis paving business can be a business opportunity for the community so that it can increase family income.